studying patterns of demand for food products in cases of low purchasing power for students at Tishreen University-Lattakia (Latakia University Journal -Biological Sciences Series, 2022)
The aim of the research is to study the consumption habits and patterns of students studying at the Tishreen University and to study the effect of low purchasing power on consumption patterns, in addition to proposing appropriate solutions to address the problem of low purchasing power for undergraduate students. The research relied on the statistics of the Food and Agriculture Organization of the World to study the food consumption patterns of the Syrian individual, in addition to designing a questionnaire consisting of three axes in order to study the consumption patterns of the students at Tishreen University and to know the most important changes that occurred to them, especially after the decrease in purchasing power.The descriptive approach was used to analyze the data to reach the goals set by using frequency tables and percentages, in addition to using the Alpha Cronbach scale to measure the credibility of the data and Likert scale in analyzing the answers. The T-test of the linked samples was used to test the research hypothesis.The results of the research showed a general decrease in the relative importance of consumption patterns among students of the College of Agriculture after the decrease in purchasing power, with the exception of the bread and grain group, as they are among the basic materials that cannot be dispensed with. Slightly due to free education in public universities. The results also showed that there were statistically significant differences in consumption patterns for students at Tishreen University before and after the decrease in purchasing power.